Does Inflation Affect Savings Non-linearly? Evidence from India. (November 2018) - Dash, Santosh K.; Kumar, Lakshmi
In the wake of the steep fall in the saving rate between 2007–2008 and 2012–2013, this article investigates to what extent inflation explains the variation in the saving rate. Most of the extant studies on saving focus on estimating the linear impact of inflation on saving; our article examines for the first time whether inflation has a non-linear impact on saving. To ascertain how inflation affects saving, we use both linear and non-linear models like the quadratic method and the Sarel (Staff Papers [Interdomestic Monetary Fund], 43, 199–215, 1996) methodology. Our findings from the linear saving model suggest that both domestic and private savings are negatively correlated with inflation, the real interest rate and the share of agriculture, and positively correlated with the growth rate. Further, higher public saving crowds out private saving, suggesting a partial Ricardian equivalence. Results from the non-linear models do not suggest a non-linear impact of inflation on saving. Thus, there is no threshold inflation in the context of the inflation–saving relationship. Instead, we find that inflation has a linear and significant negative effect on savings. The implication of not finding threshold inflation is that the central bank should control inflation, so as to promote a higher saving rate. JEL Classification: C22, E21, E31